A role for taste receptors in (neuro)endocrinology?. (19th February 2019) - Behrens, Maik; Meyerhof, Wolfgang
Abstract : The sense of taste is positioned at the forefront when it comes to the interaction of our body with foodborne chemicals. However, the role of our taste system, and in particular its associated taste receptors, is not limited to driving food preferences leading to ingestion or rejection before other organs take over responsibility for nutrient digestion, absorption and metabolic regulation. Taste sensory elements do much more. On the one hand, extra‐oral taste receptors from the brain to the gut continue to sense nutrients and noxious substances after ingestion and, on the other hand, the nutritional state feeds back on the taste system. This intricate regulatory network is orchestrated by endocrine factors that are secreted in response to taste receptor signalling and, in turn regulate the taste receptor cells themselves. The present review summarises current knowledge on the endocrine regulation of the taste perceptual system and the release of hunger/satiety regulating factors by gastrointestinal taste receptors. Furthermore, the regulation of blood glucose levels via the activation of pancreatic sweet taste receptors and subsequent insulin secretion, as well as the influence of bitter compounds on thyroid hormone release, is addressed. Finally, the central effects of tastants are discussed briefly.